Investigations on electrical parameters degradation and recovery of E-mode GaN high-electron mobility transistors under repetitive unclamped inductive switching stresses based on low-frequency noise. (23rd December 2020) - Xu, X B; Li, B; Chen, Y Q; Wu, Z H; He, Z Y; En, Y F; Huang, Y
Abstract: During no or minimal avalanche capability, the surge ruggedness of the E-mode AlGaN/GaN high-electron mobility transistors (HEMTs) with p-GaN gate has not been fully understood. This work unveils the comprehensive results from repetitive unclamped inductive switching (UIS) measurements on commercial p-gate GaN HEMTs. The Electrical parameters degradation and recovery characteristics have been investigated. Firstly, a careful study has been made about the degradation of output, transfer, gate leakage, and gate capacitance parameters of GaN HEMT devices before and after repetitive UIS pulses, which acting on the device channel. With the help of the low-frequency noises (LFNs), the test results show that the device characteristics have gradual degradation with an increase in UIS pules, including increased threshold voltage ( V th ), and decreased gate leakage current ( I gss ). Subsequently, the LFN testing is carried out with the increase of UIS pulses. Finally, the recovery characteristics of the devices are studied and the physics associated are discussed after putting the device at room temperature in the air for 1–15 d, which includes DC characteristics and trap density. These results physically confirm that the mechanism of the degradation and recovery of device characteristics, that is the charge trapping effects of electrons. After repetitive UIS stresses, the electrons are trapping and de-trapping on interfaces and in the bulk layer of devices, which can change electric field distribution below the grids. These have a strong impact on the electrical performance of devices.